2006
DOI: 10.3892/ijmm.18.1.147
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin and its metabolite, fucoxanthinol, suppress adipocyte differentiation in 3T3-L1 cells

Abstract: Abstract. Fucoxanthin is a major carotenoid found in edible seaweed such as Undaria pinnatifida and Hijikia fusiformis. We investigated the suppressive effects of fucoxanthin and its metabolite, fucoxanthinol, on the differentiation of 3T3-L1 preadipocytes to adipocytes. Fucoxanthin inhibited intercellular lipid accumulation during adipocyte differentiation of 3T3-L1 cells. Furthermore, fucoxanthin was converted to fucoxanthinol in 3T3-L1 cells. Fucoxanthinol also exhibited suppressive effects on lipid accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
147
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(153 citation statements)
references
References 35 publications
3
147
1
2
Order By: Relevance
“…Wls rich in fucoxanthin were prepared from dried seaweed powder by acetone extraction. The composition of the Wls was analyzed by high performance liquid chromatography (HPlc) as per previously published methods (15). The extracted Wls mainly consisted of glycolipids (68%), and had a fucoxanthin concentration of 10%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wls rich in fucoxanthin were prepared from dried seaweed powder by acetone extraction. The composition of the Wls was analyzed by high performance liquid chromatography (HPlc) as per previously published methods (15). The extracted Wls mainly consisted of glycolipids (68%), and had a fucoxanthin concentration of 10%.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that a Wl diet improves insulin resistance, suppressing inflammatory reactions in WAT. Our previous study revealed that fucoxanthin and fucoxanthinol (a metabolized component of fucoxanthin) affect peroxisome proliferator-activated receptor γ (PParγ) and promote gene expression related to lipid metabolism in adipocytes (4,15). Hence, it can be presumed that WLs relieve inflammation in adipose tissue, thus having an anti-diabetic effect.…”
mentioning
confidence: 99%
“…또한, punicic acid는 석류 씨에 풍부한 conjugated linolenic acid로, 암세포 증식 억제 효과 [6,7]와 항염증 [5] 효과가 있는 것으로 보고되어 있다. 최 근 여러 연구들에서 fucoxanthin과 punicic acid의 지방세포분 화 억제 작용과 고지방식이(high-fat diet)로 유도된 비만 마우 스에서의 항비만 효과가 밝혀졌다 [12,22,26]. Fucoxanthin은 3T3-L1전구지방세포에서 peroxisome proliferator-activated receptor (PPAR) gamma의 발현을 감소시킴으로써 지방세포 분화를 억제하였고, 고지방식이로 유도된 비만 마우스에서 uncoupling protein (UCP)-1의 발현을 증가시킴으로써 에너 지 소비를 촉진시켜 체중 및 식이효율, 복부부고환주위 백색 지방 등의 내장지방 무게를 유의적으로 감소시켰다 [12,20,21,22].…”
Section: 서 론unclassified
“…최 근 여러 연구들에서 fucoxanthin과 punicic acid의 지방세포분 화 억제 작용과 고지방식이(high-fat diet)로 유도된 비만 마우 스에서의 항비만 효과가 밝혀졌다 [12,22,26]. Fucoxanthin은 3T3-L1전구지방세포에서 peroxisome proliferator-activated receptor (PPAR) gamma의 발현을 감소시킴으로써 지방세포 분화를 억제하였고, 고지방식이로 유도된 비만 마우스에서 uncoupling protein (UCP)-1의 발현을 증가시킴으로써 에너 지 소비를 촉진시켜 체중 및 식이효율, 복부부고환주위 백색 지방 등의 내장지방 무게를 유의적으로 감소시켰다 [12,20,21,22]. Punicic acid는 3T3-L1전구지방세포에서 PPAR alpha와 gamma 수용체 활성을 증가시켜 공복시 혈당을 낮추 고, 당대사 능력을 개선시켰다 [10].…”
Section: 서 론unclassified
“…Phosphorylation of AKT protein, which is related to insulin signaling, was induced in the fucoxanthin-fed group. Further treatment with fucoxanthinol 3T3-L1 adipocyte cells suppress adipocyte differentiation more strongly than those treated with fucoxanthin 25 . Moreover, amarouciaxanthin A suppressed preadipocyte cell differentiation accompanied by peroxisome proliferator-activated receptor γ PPARγ and CCAAT enhancer binding protein α C/EBP α protein expression.…”
Section: Anti-diabetic Effects Of Fucoxanthinmentioning
confidence: 99%